Physical activity level and hypoglycemia in type 1 diabetes patients - Duarte, Camila Kümmel; Rodrigues, Ticiana da Costa; Merker, Aline Juliana Schneider; Brauner, Fabiane de Oliveira; de Almeida, Jussara Carnevale (Clinical and Biomedical Research, 2016)
Introduction: The recommended management for individuals with type 1 diabetes (T1D) includes an intensive treatment with insulin therapy and the practice of regular exercise. However, this association is related with hypoglycemia episodes. Objective: The aim of this study was to perform a cross-sectional evaluation of the association between the physical activity (PA) level and hypoglycemia episodes reported in patients with T1D. Methods: Adult outpatients with T1D had their PA level assessed by the International Physical Activity Questionnaire (long form), considering the intensity of the physical activity (vigorous, moderate and/or walks) in daily activities, such as at work, means of transport, domestic activities and at leisure, and answered questions about self-care and hypoglycemia episodes. Results: The study included 126 patients who presented the following characteristics: mean age of 35 (28-47) years old and 16 (11- 24) years of diabetes duration, 55% women, HbA1c=9.3 ± 2.1%, and body mass index = 25.0 ± 4.2kg/m2. Very active patients had lower values of glucose and LDL-cholesterol when compared with the less active group. A greater proportion of active (48.1%) and very active patients (66.7%) reported practicing exercise regularly when compared with the less active subjects (13.3%; P=0.003). Less active patients had a three-fold chance of reporting hypoglycemia episodes when compared with very active patients (OR=3.49; CI 95%: 1.26-9.70; P=0.016). Conclusions: Less active adults with T1D presented more hypoglycemia, probably due to the practice of informal moderate and/or vigorous activities without specific self-care. Keywords: Exercise; self-care, blood glucose